THE ROLE OF SCHOLARSHIPS ON LEARNING MOTIVATION - Ramadhianti, Raden Heryaningtias; Soegoto, Dedi Sulistiyo (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
Scholarships in the field of education serve as financial assistance to help students pursue education according to their talents and interests. This research aims to explore the impact of scholarships on students’ academic achievement through increased learning motivation. Using a qualitative method, we surveyed 25 scholarship recipients from five study programs. The results show that scholarships play a significant role in enhancing students’ learning motivation, ultimately improving their Cumulative Grade Point Average (CGPA) each semester while receiving the scholarship. This financial support enables students to focus on their studies without the distraction of tuition fees. Additionally, scholarships are also seen as motivators for students to excel academically. However, being a scholarship recipient also brings mental burden due to societal perceptions associating scholarships with high academic ability.